2019
DOI: 10.1002/mgg3.836
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Tay‐Sachs disease carriers by full‐exon sequencing with novel variant interpretation outperforms enzyme testing in a pan‐ethnic cohort

Abstract: Background Pathogenic variants in HEXA that impair β‐hexosaminidase A (Hex A) enzyme activity cause Tay‐Sachs Disease (TSD), a severe autosomal‐recessive neurodegenerative disorder. Hex A enzyme analysis demonstrates near‐zero activity in patients affected with TSD and can also identify carriers, whose single functional copy of HEXA results in reduced enzyme activity relative to noncarriers. Although enzyme testing has been optimized and widely used for carrier screening in Ashkenazi Jewish (AJ) individuals, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A recent study demonstrated that for both AJ and non-AJ populations, clinical performance of NGS-based CS was better than enzymatic methods to screen for Tay-Sachs. 31 Additional studies are needed to clarify whether the enzyme studies are still needed for rare variants. Similarly, screening for hemoglobinopathies has traditionally involved a complete blood count, red blood cell indices, reflex hemoglobin electrophoresis, and other testing if there is a suspicion of a hemoglobinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that for both AJ and non-AJ populations, clinical performance of NGS-based CS was better than enzymatic methods to screen for Tay-Sachs. 31 Additional studies are needed to clarify whether the enzyme studies are still needed for rare variants. Similarly, screening for hemoglobinopathies has traditionally involved a complete blood count, red blood cell indices, reflex hemoglobin electrophoresis, and other testing if there is a suspicion of a hemoglobinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been extremely effective, e.g., in reducing the incidence of Tay-Sachs disease (MIM: 272800) in Ashkenazi Jewish populations around the world. 9,10 ECS is an extension of this approach that involves simultaneous screening for many pathogenic variants responsible for a broad range of diseases in the general population. This broadscale approach to screening is achieved by sequencing the entire genomes (genome sequencing) or the fraction of the genome that encodes proteins-the exome (exome sequencing)-of prospective parents.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of HEXA isoenzyme levels in TSD symptomatic individuals is deficient while that of β hexosaminidase B (HEXB) isoenzyme, is either normal or elevated. Therefore, an assessment of β hexosaminidase enzyme activity in peripheral leukocytes, cultured fibroblasts or lymphoblasts is the test widely used interna-tionally to diagnose the disease [4]. Recently, Next Generation Sequencing (NGS) has been proposed as an alternative screening method for TSD specially in populations with highly diverse ethnic origin.…”
Section: Zusammenfassungmentioning
confidence: 99%